Factors Influencing the Social Health of Employees of the Ministry of Health and Medical Education in Iran - Seyede Maryam Haery; Hadi Tehrani; Alireza Olyaeimanesh; Saharnaz Nedjat (Iranian Association of Health Education and Health Promotion, 2016)
Background and Objective: Indeed the development of health promotion programs in the community would result in ineffective solutions if social and cultural backgrounds are not considered. Therefore, this study was conducted to assess the level of social health and factors influencing the staff employees of the Ministry of Health and Medical Education in Iran. Materials and methods:  The study was a descriptive- analytical one in which 257 employees of the Ministry of Health and Medical Education in Iran were selected by stratified random sampling. In order to measure the social health of the employees, Keyes social health questionnaire was used. This questionnaire measured five social health components- social cohesion, social prosperity, social acceptance, participation and social adaptation. The data analysis was conducted using Non-parametric correlation (c2) and Kendall's test by SPSS 20 with the significance level of 0.05. Results: Most of the participants (51.7%) had medium social health, and 17.8% had low social health. There was a significant correlation between social health and gender, education and accommodations (p < 0.05); but no significant relationship was found between social health and age, marital and employment status. Conclusion: Health system will have a good performance if the issues and needs of employees are considered in designing and managing it. The results of this study showed the importance of health education and health promotion intervention in the field of social health among staff, especially the staff of the Ministry of Health and Medical Education in Iran. Paper Type: Research Article.